Not Something, Not Nothing, Not Shakespeare: Digitized Playbooks and the Question of Access in the Undergraduate Literature Classroom - Jordan Windholz (Humanities, 2019)
The digital divide is deeply felt by undergraduate students in resource-restricted universities, but creative, if also labor-intensive, solutions exist for instructors negotiating paywalls and other institutional impediments. In this essay, I argue that teaching early modern drama outside the restraints of the Shakespearean archive and through a host of digital archives, databases, and tools not only engages students in inquiry-based, active learning but also cultivates a critical sense of how digital tools obviate and exacerbate questions of access. To make my case, I describe how I designed and taught a course on non-Shakespearean drama for English majors at Shippensburg University, one of Pennyslvania’s state-funded universities. After describing the mechanics of the course, I further theorize and examine the ways centering digital archives, databases, and tools as course texts enables students to think critically about the content available through these resources as well as the information hierarchies and receptions histories they promulgate.